Local spatiotemporal dynamics of a simple aridity index in a region susceptible to desertification - Costa, Ana Cristina (2019)
Costa, A. C., & Soares, A. (2012). Local spatiotemporal dynamics of a simple aridity index in a region susceptible to desertification. Journal Of Arid Environments, 87, 8-18. https://doi.org/10.1016/j.jaridenv.2012.05.005